Decreased mRNA expression of NR1H3 and ABCA1 in pulmonary tuberculosis patients from population of Punjab, India - Kumari, Anju; Saini, Varinder; Kumar, Vijay (Molecular biology reports, 2024)
Background Mycobacterium tuberculosis (MTB) is the causative organism of tuberculosis. Cholesterol is a crucial carbon source required for the survival of MTB in host cells. Transcription factor NR1H3 along with its important target genes ABCA1 and ApoE play important role in removal of extra cholesterol from cells. Changes in the gene expression of NR1H3 , ABCA1 and ApoE can affect cholesterol homeostasis and thus the survival of MTB in host cells.Therefore, the present study was designed to analyze the mRNA expression of NR1H3 , ABCA1 and ApoE in pulmonary TB (PTB) patients from the population of Punjab, India. Methods and results In this study, mRNA expression of the transcription factor NR1H3 and its target genes ABCA1 and ApoE was analyzed in 89 subjects, including 41 PTB patients and 48 healthy controls (HCs) by real-time quantitative PCR. It was found that the mRNA expression of both NR1H3 and ABCA1 genes was significantly lower in TB patients than in HCs ( p < 0.001). Even after sex-wise stratification of the subjects, mRNA expression of NR1H3 and ABCA1 was found to be down-regulated in both male and female TB patients. No significant difference was observed in expression of ApoE ( p = 0.98). Conclusions The present study found that the mRNA expression of NR1H3 and ABCA1 is down-regulated in TB patients from Punjab state of India.